Limited transmission of avian influenza viruses, avulaviruses, coronaviruses and Chlamydia sp. at the interface between wild birds and a free-range duck farm - Chloé Le Gall-Ladevèze; Benjamin Vollot; Julien Hirschinger; Laëtitia Lèbre; Rachid Aaziz; Karine Laroucau; Jean-Luc Guérin; Mathilde Paul; Julien Cappelle; Guillaume Le Loc’h (Veterinary Research)
Abstract Recent outbreaks of highly pathogenic avian influenza in Europe have raised questions regarding the epidemiological role of commensal wild birds on free-range poultry farms. This study aimed to assess the prevalence of avian influenza viruses (AIV), avulaviruses, coronaviruses and Chlamydia sp. in commensal wild birds on a free-range duck farm in southwestern France and to evaluate possible transmission events at the wild‒domestic interface. From 2019 through 2021, a longitudinal study was conducted on wild birds, domestic ducks and their shared environment on farms. Commensal wild birds were captured and sampled for blood and swabs, and fresh feces from cattle egrets visiting the farm were collected. In parallel, domestic ducks were sampled, and environmental samples were collected. The presence of the four pathogens was tested by q(RT-)PCR, and the immunity of wild birds to AIV and Newcastle disease virus (NDV) was tested by ELISA. Wild birds were found to shed AIV and Chlamydia only, with a low prevalence (< 3%). The seroprevalence rates were less than 10% for AIV and less than 4.5% for NDV. No significant temporal trend was identified. Ducks and their environment frequently test simultaneously positive for the same pathogens (19 to 44% of flocks), mostly during fall‒winter. In addition to unrelated temporal patterns, the identification of pathogens in wild birds seemed unrelated to that in domestic ducks. These results suggest a low transmissibility of the avian pathogens tested in our study at the wild‒domestic interface and highlight the limited contribution of commensal wild birds in comparison with free-range poultry to the global microbiological pressure on the environment.